Techno-Resiliency in Education A New Approach For Understanding Technology In Education - Graham, Rob (Springer International Publishing : Imprint: Springer, 2016)
This book formulates a greater understanding of how to enable a capacity for building social professional practice related to technology-enriched teaching and learning (TETL) specific, but not limited to, educational settings. This book comes at a time when many in education are struggling to provide a technology enriched learning experience for students who are entering classrooms with high expectations for such an experience. The focus on the protective factors and identified resilient professional practices, instead of on well documented and commonly cited risk factors and barriers that impede the effective integration of TETL, represents a distinguishing feature of this work. By attempting to better understand and document how two schools that were classified as resilient in their use of technology have been able to overcome risk factors (e.g., budgetary constraints, a lack of resources, a lack of training, technological support issues), this book will offer the unique concept of techno-resiliency and some of its deeper insights and strategies.